Testiranje biološke učinkovitosti feromona i klopki za ulov mediteranskog potkornjaka Orthotomicus erosus (Coleoptera, Curculionidae) : Testing of biological effectiveness of pheromones and traps for catch of mediterranean bark beetle Orthotomicus erosus (Coleoptera, Curculionidae) - Pernek, Milan (Array, 2020)
In the Aleppo pine forests at the Croatian Mediterranean in 2017, a Mediterranean bark beetle (Orthotomicus erosus) appeared in population densities that had not been recorded before and until then was not considered a significant pest in that area. Natural enemies are not able to follow a sudden increase of the bark beetle population, which results in rapid increase of drying trees. As a part of the suppression of the Mediterranean bark beetle in 2018, pheromone traps have been installed in Croatia for monitoring purposes. Although there are multiple options for applying different types of traps and pheromone preparations for the Mediterranean bark beetle, so far the differences in catches of different types of traps and their selectivity have not been investigated. In 2019, 40 pheromone traps were placed in the Forest Park ​​Marjan (Split) on 196 ha of forest area. A pairs of pheromone preparations Pheroprax and Erosowit were compared, a system of three traps (Triplet) with a single flight barrier trap as well as the modified wet flight barrier trap with a regular flight barrier trap. In addition to the average number of catches in pheromone traps, particular attention was given to selectivity. Two predator species Tanasimus formicarius and Temnochila caerulea were found in traps, with T. formicarius in insignificant quantities relative to T. caerulea. The results indicate that Erosowit exhibits significantly higher catches compared to Pheroprax and is significantly more selective. Pheroprax has a very high catches of T. caerulea predators and is not recommended for practical use. The Triplet had only slightly better catches compared to the single flight barrier trap, but also showed slightly better selectivity. The Triplet did not show the expected effect due to the amount of the catch, which was slightly higher than in the single trap, but not significantly in order to recommend their use.